(untitled) (TAJ: Journal of Teachers Association, 2018)
Maternal, fetal complications are correlated with hypertensive disorders during pregnancy. In this context, maternal blood uric acid level is reported to be one of the prognostic factors in determining the perinatal out come. The purpose of the present study is to estimate serum uric acid levels in preeclamptic, eclamptic and normotensive groups to identify woman who are at high risk of developing the disease early in pregnancy. The study may provide possible biochemical parameter in preeclampsia and eclamsia. This is because early identification of biochemical markers of the disease would not only facilitate to identify those at increased risk for pre eclampsia but also help to determine those patients likely to benefit from interventional measures. A total 50 patients were selected and categorized into three groups. 30 among 50 woman, were pregnancy induced hypertension BP>140/90 mm Hg. Who were as the experimental group and remaining 20 were normotensive (BP <140/90 mm Hg) taken as control (n=20). The experimental group was further categorized into two groups having 20 woman in preeclampsia (n=20), and Ten in eclampsia (n=10). The serum uric acid level studied in various study group showed a significant in pre eclampsia (n=20) and the eclamptic(n=10). The serum uric acid level for women with pre eclamsia 5 mg/dl-6.3 mg/dl n-10) were significant higher than those of controls (4-56 mg/dl n=20) more ever, it was experimentally found that the individual values of observed serum uric acid in preeclamptics and eclamptic were relatively higher than those of the average values of normotensive. In the setting of chronic hypertension, however a serum uric acid level at> or =5.5 mg/dl could identify women with increased likelihood of having superimposed pre eclampsia. A comparison between three groups related that hyperuricemia in patient with preeclampsia,eclampsia is certainly a risk factor for several perinal and maternal complications. TAJ 2014; 27(1): 24-28